2019
DOI: 10.1007/s10926-019-09868-9
|View full text |Cite
|
Sign up to set email alerts
|

Employment in Personality Disorders and the Effectiveness of Individual Placement and Support: Outcomes from a Secondary Data Analysis

Abstract: Purpose Personality disorders (PDs) are associated with severe functional impairment and subsequent high societal costs, increasing the need to improve occupational functioning in PD. Individual placement and support (IPS) is an effective, evidence-based method of supported employment, which so far has been tested in various mixed patient populations with severe mental illness (SMI, including PDs). However, the effectiveness of IPS for PDs per se remains uninvestigated. Methods Data from the SCION trial were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…While traditionally, in Germany, the first step in vocational rehabilitation is to treat and then engage people on the sheltered labor market, only a small percentage of patients can thus finally be integrated into the general labor market [49]. In contrast, supported employment programs such as individual placement and support (IPS) follow the strategy "place-and-treat-/ train" instead of "train/treat-then-place" concurrently offering care and at the same time helping in finding employment [50,51]. Thereby, specific barriers to employment, such as distance to the labor market and stigma, are dealt with.…”
Section: Discussionmentioning
confidence: 99%
“…While traditionally, in Germany, the first step in vocational rehabilitation is to treat and then engage people on the sheltered labor market, only a small percentage of patients can thus finally be integrated into the general labor market [49]. In contrast, supported employment programs such as individual placement and support (IPS) follow the strategy "place-and-treat-/ train" instead of "train/treat-then-place" concurrently offering care and at the same time helping in finding employment [50,51]. Thereby, specific barriers to employment, such as distance to the labor market and stigma, are dealt with.…”
Section: Discussionmentioning
confidence: 99%
“…Further, economic insecurity is common among patients with severe mental disorders [ 43 , 44 ], as well as functional impairment, which prevents them from living an independent life [ 45 ]. Despite this evidence, working interventions, which can highly enhance functional impairment [ 46 ], have not been widely used in the IHB group. The most of IHBs were indeed focused on the living axis [ 47 ], which comprehended a variety of “housing opportunities”, such as therapeutic–rehabilitative dwellings, individual and grouped flats, and personalized support at home.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the diverse association between these clinical diagnoses and IHB is not easy to explain. Both disorders, in fact, are associated with functional impairment, unemployment, and interpersonal deficits [ 45 , 46 ]. Fifthly, we did not include pharmacological assessment, which could have affected HoNOS ratings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Type of the mental issue is also critical as it seems to be more effective in some disorders and less and in others (21,84). A systematic review of studies assessing IPS efficacy in individuals with substance use disorders found that episodic treatment of the disease and risk of relapse of the mental disease were among important barriers in implementing IPS (22).…”
Section: Barriers and Facilitators Of Successful Ips Implementation And Employmentmentioning
confidence: 99%